Cognitive behaviour therapy for long-term frequent attenders in primary care: a feasibility case series and treatment development study - Malins, Samuel; Kai, Joe; Atha, Christopher; Avery, Anthony; Guo, Boliang; James, Marilyn; Patel, Shireen; Sampson, Christopher; Stubley, Michelle; Morriss, Richard K. (Royal College of General Practitioners, 2016)
Background: Most frequent attendance in primary care is temporary. Long-term frequent attendance may be suitable for psychological intervention to address health management and service use.